2022
DOI: 10.1155/2022/2310080
|View full text |Cite|
|
Sign up to set email alerts
|

The Relationship between Antenatal Corticosteroid Administration-to-Delivery Intervals and Neonatal Respiratory Distress Syndrome and Respiratory Support

Abstract: Background. Administration of antenatal corticosteroids (ACSs) is an effective strategy for managing preterm infants, which improves neonatal respiratory distress syndrome (NRDS) and attenuates the risk of neonatal mortality. However, many preterm infants are not exposed to a complete course of ACS administration, and the effects of different ACS-to-delivery intervals on NRDS and respiratory support remain unclear. Therefore, this study explored the relationship between ACS-to-birth intervals and NRDS and resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 32 publications
(42 reference statements)
0
4
0
Order By: Relevance
“…Instead, the diminished demonstration of benefit may stem from a reduction in disease burden, making it challenging to highlight this advantage. Late-preterm neonates, although less prone to Respiratory Distress Syndrome (RDS) than those born before 34 weeks, remain at risk for respiratory morbidities from alternative causes (Li et al, 2022b;Taleghani et al, 2020) The lower requirement for mechanical ventilation in the antenatal steroid group further highlights the clinical significance of this approach, mitigating the risk of respiratory complications and associated morbidities in preterm infants (Asztalos et al, 2020;Li et al, 2023;Oladapo et al, 2022). While bronchopulmonary dysplasia (BPD) rates were numerically lower in the antenatal steroid group, the lack of statistical significance may be influenced by factors such as the intricate nature of BPD development, variations in postnatal management, and the relatively modest sample size (Morhart et al, 2022;Mpinga et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Instead, the diminished demonstration of benefit may stem from a reduction in disease burden, making it challenging to highlight this advantage. Late-preterm neonates, although less prone to Respiratory Distress Syndrome (RDS) than those born before 34 weeks, remain at risk for respiratory morbidities from alternative causes (Li et al, 2022b;Taleghani et al, 2020) The lower requirement for mechanical ventilation in the antenatal steroid group further highlights the clinical significance of this approach, mitigating the risk of respiratory complications and associated morbidities in preterm infants (Asztalos et al, 2020;Li et al, 2023;Oladapo et al, 2022). While bronchopulmonary dysplasia (BPD) rates were numerically lower in the antenatal steroid group, the lack of statistical significance may be influenced by factors such as the intricate nature of BPD development, variations in postnatal management, and the relatively modest sample size (Morhart et al, 2022;Mpinga et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Previous study demonstrated a clear statistical and clinical benefit of corticosteroids on RDS from 34 weeks + 0 days gestation, but not with other primary outcomes. Thus, in very late preterm gestation women (from 35 weeks + 0 days) the use of antenatal corticosteroids needs to be considered in light of the balance of risks and benefits Li et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%